Movimentos sociais de ocupação da Grande Aracaju : ritos, símbolos e místicas - Rocha, Marcos Andrade (2021)
The research selected the two occupational social movements with the highest number of occupations in Greater Aracaju, the Organized Movement of Urban Workers - MOTU, and the Movement of Homeless Workers - MTST. The research main purpose was to analyze the relationship between the rituals and symbols of the Homeless, and their strategies in the struggle for housing. The central question that guided the research was to know "how do the Homeless relate their rites and symbols with their strategies in the struggle for housing?" The hypothesis adopted is an insight that there is a relationship among the rites and symbols (on the one hand) and the fighting strategies (on the other hand) of the Homeless movements, and the ritualization of the struggle for housing would contribute to the strengthening of the social link between the homeless, generating cohesion to the group. Methodologically, the research was based mainly on two complementary actions: a) the participant observation, ethnographic; b) semi-structured interviews, with social actors active in the studied movements. The results obtained showed that the ritualization of the struggle for housing occurs through the use of symbolic resources (flags, shirts, exaltation of food and work tools) and rituals (chants, cries, celebrations), especially in the “ritual moments” they call mystics. In a conclusive way, I observed that the Homeless Movements analyzed, MOTU and MTST, promoting their occupations, use rites and symbols, in the construction of social cohesion among the occupants, in favor of the struggle for housing. This cohesion, this bond between the “homeless”, built amidst the mystics that occurred in their occupations, under the banners of the movements and in their central barracks, between people, songs and celebrations, is fundamental to the confrontation necessary for the popular housing conquest. Through the rites, symbols and mystics, the “Homeless Movements” establish their social ties.